Research on the role of the attitudes of Vietnamese consumers towards their intentions to use mobile money - Thuy Hang Vu Thi (Global Business & Finance Review (GBFR), 2024)
Purpose: The research was conducted to determine the role of the attitudes of Vietnamese consumers towards the intention to use mobile money to make recommendations for solutions to improve the effectiveness of this activity. Design/methodology/approach: It analyzed 307 surveys from consumers living and working in Vietnam. A research model was built that was based on the theory of technology acceptance model (TAM) and the theory of planned behavior (TPB). The author considered six constructs, including self-efficacy, perceived ease-of-use, technology anxiety, perceived usefulness, attitude toward mobile money, and intention to use mobile money. The data is analyzed with a partial least squares structural equation model (PLS-SEM) using SmartPLS 3.0 software. Findings: The r esult indicated that s elf-efficacy (SE) sig nificantly a nd d irectly a ffects t he p erceived e ase of u se (PEOU), indirectly affects the attitude toward mobile money (AT), and intention to use mobile money of Vietnamese consumers (IU). The PEOU and perceived usefulness (PU) significantly and directly affect the AT, and indirectly affect IU. In contrast, technology anxiety (TA) showed no effect on the PU. In addition, the AT has a strong effect on the IU. Research limitations/implications: This paper presents significant implications, particularly for the digital economy, which is currently permeating every facet of human existence. The article also suggested future research directions, including expand the scope of the research, the sample size, and the addition of other factors to supplement and complete the model. Originality/value: The article closes a perceived gap in the mobile money literature by using model measurement to demonstrate the mobile money intention of Vietnamese consumers.
Keywords: 650; Mobile money; Role of attitude; Intention to use; Vietnamese consumer